1990
DOI: 10.1152/ajprenal.1990.259.5.f839
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of cerebral NaCl concentration can abolish mineralocorticoid escape

Abstract: The effect of lowering cerebrospinal fluid (CSF) Na concentration on renal Na excretion (UNaV) was investigated in conscious sheep undergoing mineralocorticoid escape induced by intravenous infusion of aldosterone (20 micrograms.ml-1.h-1) for 3 days. On the 3rd day of aldosterone administration, when plasma and CSF Na concentration and mean arterial blood pressure (MABP) were increased as a result of the mineralocorticoid treatment, a reduction in the CSF Na concentration was induced by infusing a Na-free solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 0 publications
1
15
0
Order By: Relevance
“…It has been reported that elevation of the sodium concentration of cerebrospinal fluid by intraventricular injection of hypertonic NaCl solutions caused hyperten- sion in rats 37 -38 and that reduction of cerebrospinal fluid sodium levels by intracerebroventricular infusion of isosmotic NaCl-free mannitol solution resulted in significant reductions of MBP. 36 This observation supported our hypothesis that the Ang II-induced hypertension in mutant BN-Ka rats may be attributable to sodium retention caused by aldosterone release. The absence of any change either in the serum concentrations of potassium and creatinine or in their urinary excretion eliminated the possibility that sodium reten- tion was caused by impaired kidney function, which was observed after infusion of the higher dose of Ang II.…”
supporting
confidence: 84%
See 1 more Smart Citation
“…It has been reported that elevation of the sodium concentration of cerebrospinal fluid by intraventricular injection of hypertonic NaCl solutions caused hyperten- sion in rats 37 -38 and that reduction of cerebrospinal fluid sodium levels by intracerebroventricular infusion of isosmotic NaCl-free mannitol solution resulted in significant reductions of MBP. 36 This observation supported our hypothesis that the Ang II-induced hypertension in mutant BN-Ka rats may be attributable to sodium retention caused by aldosterone release. The absence of any change either in the serum concentrations of potassium and creatinine or in their urinary excretion eliminated the possibility that sodium reten- tion was caused by impaired kidney function, which was observed after infusion of the higher dose of Ang II.…”
supporting
confidence: 84%
“…Intravenous administration of aldosterone was reported to increase sodium concentrations in plasma and cerebrospinal fluid and to raise MBP. 36 The hypertension in mutant BN-Ka rats was not caused by their arterioles being more sensitive, because the blood pressure response to bolus intravenous injection of Ang II under pentobarbital anesthesia in these rats was not different from that in normal BN-Ki rats. Some genetic bias in mutant BN-Ka rats, related to arteriolar hypersensitivity to Ang II, may therefore be ruled out.…”
mentioning
confidence: 91%
“…First, increased OSM acting centrally is pressor in part by increasing arginine vasopressin release 20 and in part by activation of the sympathetic nervous system. 1 Second, Pennington and McKinley 21 reported that, in aldosterone-treated sheep, reduction of brain OSM by intracerebroventricular infusion of mannitol slowly decreases BP. Third, in DOCA-treated rats consuming excess salt, c-fos expression is induced in multiple osmosensitive circumventricular organs, 11 brain regions lacking a blood-brain barrier.…”
Section: Discussionmentioning
confidence: 99%
“…The pressor and sympathetic responses to ANG II are well known to be enhanced by a high-salt intake (22). In addition, aldosterone has been shown to increase cerebrospinal fluid sodium concentration, and reducing this leads to a fall in blood pressure (23), further demonstrating the important role of increased brain sodium in mineralocorticoid hypertension. Moreover, the enhanced pressor response to ANG II in PA patients may also be due to a greater increase in sympathetic neural outflow.…”
Section: Discussionmentioning
confidence: 99%